E-Commerce Web Design to Improve Marketing and Sales for Micro Small and Medium Enterprises During the Covid-19 Pandemic (Case study: Rokusan Addict’s) - Jeremias Yohanes Semok Rahasomar; Dani Hamdani (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
The utilization of great marketing methods for MSMEs to increase sales can make it easier for sellers and consumers to reach them even during the COVID-19 pandemic. There is a decrease in public interest in purchasing products that are influenced by manual marketing methods. The utilization of information technology in running a business or frequently known as e-commerce for a small company can provide flexibility in production, enabling faster delivery to customers. During the pandemic, there was a change in the consumption pattern of people's goods and services from offline to online. MSME actors must have difficulty in achieving the targets that must be achieved when the economy is disrupted. This change in the pattern should be followed by Micro, Small, and Medium Enterprises to survive and develop so that they can face new normal conditions. The System Design is based on the needs of existing users in business activities related to Rokusan Addict's sales and marketing conditions. This design uses the data collection method, which includes the observation method and the interview method. The analysis process used is PIECES ANALYSIS and System Design which includes Design, Implementation, and Maintenance. At the testing stage, this study uses Black Box testing to test whether the input and output results are appropriate or not. The overall results of using this Black Box test achieved a perfect fit and it was concluded that the design of the e-commerce website created was acceptable and had positive functionality for users.